Association between organizational citizenship behavior and patient safety culture from nurses' perspectives: a descriptive correlational study - Marzyeh Jafarpanah; Behrooz Rezaei (BMC, 2020)
Abstract Background Nurses play a key role in providing patient safety. It is known that patient safety requires the improvement of patient safety culture, which can be a difficult process. One of the current challenges of hospitals is to explore the ways to improve patient safety culture. Organizational citizenship behaviors are one of the factors, which can develop organizational culture including safety culture; however, its role is not well established. Methods In this cross-sectional study, a stratified random sample of 214 nurses was selected from a largest teaching hospital in west of Iran. The institutional research board approved the study protocol. Data were collected using three self-report questionnaires: demographic information; hospital survey on patient safety culture (HSPSC); and organizational citizenship behaviors questionnaire. Data were analyzed using Spearman's correlation coefficient test in SPSS (α < 0.05). Results Organizational citizenship behaviors were found to be at an intermediate level (56.84 ± 16.22). However, some of its dimensions, including sportsmanship, civic virtue, and courtesy, were at weak levels (< 50%). The mean percentage of positive responses to the patient safety culture was 49.00 ± 14.01. The patient safety culture had significant positive correlations with organizational citizenship behaviors (r = 0.349, P = 0.001) and dimensions of altruism (r = 0.255, P = 0.001), civic virtue (r = 0.434, P = 0.001), and courtesy (r = 0.214, P = 0.001). Conclusion Our findings proposed the hypothesis that OCB has a statistical significant impact on PSC. Low levels of civic virtue, sportsmanship and courtesy behaviors may be indicative low nurses' interest in participating in organizational affairs and nurses' low attention to measures that prevent harm to their organization. It is recommended that nursing managers focus more on these dimensions, identifying influintioal factors and taking appropriate management measures to promote these behaviors. If our findings are confirmed in future studies, nursing managers can consider the development of organizational citizenship behaviors as one of the managerial approaches for promoting a patient safety culture.